Lettere 1942-1978 Con un'appendice di testi dispersi - Macrí, Oreste (Moderna/Comparata, 2016)
Against the background of the cities of Lecce, Parma and Florence (Macrì's well-known "Dimore vitali"), between the 1940s and the 1970s, an almost forgotten author (poet, translator from French, writer) and his "teacher" stand out among the fiercest critics of the twentieth century. There are many stories intertwining in the 142 epistolary pieces collected in this volume, carefully transcribed and annotated by Dario Collini. Personal stories (particularly letters are entrusted with the unprecedented and intriguing portrait of a multifaceted, complex, elusive Pagan) and collective stories, such as those told by «Libera Voce» and «Critone», which count among the cultural initiatives that helped bring the peripheral reality of Salento closer to the major literary centres of the peninsula. Along a wide chronological span, the story of a deep friendship is also revealed, which did not claim to erase the distance between the two correspondents, but which would continue over time nevertheless, nourished by "gratitude", "esteem" and "trust".